Structural studies on proteins involved pre-mRNA 3’-end processing. - Li, Sheng Jin. (2010)
Pre-mRNA 3’-end processing is crucial in eukaryotes in pre-mRNA maturation which affects cell growth and viability. Many protein factors are involved in this 3’-end processing machinery, Symplekin is one of them. There was no structural information reported for full length symplekin to date and how it interact with other core factors in 3’-end processing remains unknown. In this project, cloning and expressing of symplekin full length (starting from residue 17) and symplekin 17-1081(with C’-terminal trunked) were performed using Baculovirus Expression Vector Systems. Expression was successful and expression level was good. However the symplekin appeared insoluble even with 1% detergent added. This prevents the protein from being crystallized. In the future, try to express symplekin with further C’-terminal trunked may increase the solubility. Another solution could be co-express symplekin with two other core factors in 3’-end processing machinery, CPSF73 and CPSF100, this may give soluble complex which could be analyzed by X-ray crystallography for structural information.